2020
DOI: 10.1017/s1479262120000350
|View full text |Cite
|
Sign up to set email alerts
|

Effects of salinity stress on proline content and expression ofΔ1-pyrroline-5-carboxylate synthaseandvacuolar-type H+subunit Egenes in wheat

Abstract: To evaluate the responses of some important agronomic traits of 14 bread wheat cultivars, a split plot experiment was conducted based on a randomized complete block design under non-stress, moderate and severe salinity stress conditions. In this study, Backcross and Roshan were identified as the most salinity-tolerant cultivars, while Mihan and Shirudi were considered as the most salinity-sensitive cultivars. The proline content, as well as Δ1-pyrroline-5-carboxylate synthase (P5CS) and vacuolar-type H+-ATPase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Numerous studies have tried to link the increase of soluble sugars to salinity tolerance and the present result agrees with results from wheat genotypes treated with higher salinity level resulted in a significant increase in sugars and proline in some genotypes (Dadkhah and Rassam, 2016;Akbar et al, 2021Akbar et al, , 2022. Simultaneously, proline is also a critical component for osmoprotection in many plants, and one of the most common responses of many plants subjected to abiotic stresses is its accumulation (Goharrizi et al, 2020;Liu et al, 2020;Masarmi et al, 2023). It has been reported that proline plays a protective role in plants exposed to diverse stresses and is thought to be acting as a cellular osmotic regulator.…”
Section: Discussionsupporting
confidence: 88%
“…Numerous studies have tried to link the increase of soluble sugars to salinity tolerance and the present result agrees with results from wheat genotypes treated with higher salinity level resulted in a significant increase in sugars and proline in some genotypes (Dadkhah and Rassam, 2016;Akbar et al, 2021Akbar et al, , 2022. Simultaneously, proline is also a critical component for osmoprotection in many plants, and one of the most common responses of many plants subjected to abiotic stresses is its accumulation (Goharrizi et al, 2020;Liu et al, 2020;Masarmi et al, 2023). It has been reported that proline plays a protective role in plants exposed to diverse stresses and is thought to be acting as a cellular osmotic regulator.…”
Section: Discussionsupporting
confidence: 88%
“…As a result of this osmotic stress, the plants respond to an increased accumulation of proline (Table 4). Increased salt concentration in the environment causes an increase in plant proline accumulation (Goharrizi et al, 2020). Proline accumulation for the plant will differ depending on its resistance to osmotic stress.…”
Section: Discussionmentioning
confidence: 99%
“…The knockout of P5CS has indicated that it is necessary for mitochondrial respiratory complex organization [ 61 ]. With the development of research, P5CS in wheat has been found to respond to changes in salinity in the environment [ 62 ]. However, the expression profile of P5CS in wheat is the complete opposite of Mn-P5CS in M. nipponense under hypoxia.…”
Section: Discussionmentioning
confidence: 99%